The Chronic Effects of Salinity in the Biology of ?? Rotifers Brachionus calyciflorus Pallas (Baghdad Science Journal, 2004)
The present study included the effect of chronic exposure for two concentrations of NaC? salt on the biology of fresh water zooplankton species Brachionus calyciflorus (from ^otifera). The concentrations 0.5 , 0.75%o were used for chronic exposure to investigate its effects on the life tables, range of the rate of expectation for further life and reproduction. The rotifer B. calyciflorus was sensitive to salinity and may tried to protect the species by increasing the size (2.22 ind./clutch lor control group and 2.9? for 0.5%o concentration) and number of clutches produced ?.1? clutch/female for control group and 2.9 ' ' ' for 0.75 %0 concentration) beside stimulation the animal to produce the first clutch of eggs earlier? ? small reduction in mean longevity of the animal was noticed (8.1 day for control grou^ and7. ? day for 0.75 %0 concentration) while there was no effect on its average length and daily increasing during its life span